Evolution of Holdfast Diversity and Attachment Strategies of Ediacaran Benthic Macroalgae - Wang, Xiaopeng; Wu, Mengyin; Wan, Bin; Niu, Changtai; Zheng, Wentao; Guan, Chengguo; Pang, Ke; Chen, Zhe; Yuan, Xunlai (Frontiers in Earth Science, 2021)
Holdfast morphologies and attachment strategies of benthic macroalgae are somewhat plastic and controlled by both the substrate condition and species. Six forms (tapered base, globose holdfast, composite globose holdfast, discoidal holdfast, rhizoids and horizontal rhizomes) of attachment structures of Ediacaran benthic macroalgae are recognized from the early Ediacaran Lantian biota and late Ediacaran Miaohe biota in South China based on functional morphology. Each form is considered either adapted to firm substrates that dominate the Precambrian seafloor, or soft substrates that are more common in the Phanerozoic. The results show a diversification in both holdfast morphology and attachment strategies of macroalgae during the Ediacaran Period. In the early Ediacaran Lantian biota, none of the benthic macroalgae is adapted to soft substrates, while in the late Ediacaran Miaohe biota, a significant number (41%) of species are adapted to relatively soft substrates. This shift might be an adaptive response to the diversification of macroalgae and a changing substrate condition during the Ediacaran Period: the decline of microbial mat and increase of water content in the sediments in the Ediacaran.